Calculus of variations, classical and modern lectures given at a summer school of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Bressanone (Bolzano), Italy, June 10-18, 1966 - C.I.M.E. Summer School Bressanone, Italy) (1966; Conti, Roberto 1923-; SpringerLink (Online service). (Heidelberg, Germany Springer Berlin, 2010)
quière: Quelques aspects géométriques des processus optimaux.- C. Castaing: Quelques problèmes de mesurabilité liés à la théorie des commandes.- L. Cesari: Existence theorems for Lagrange and Pontryagin problems of the calculus of variations and optimal control of more-dimensional extensions in Sobolev space.- H. Halkin: Optimal control as programming in infinite dimensional spaces.- C. Olech: The range of integrals of a certain class vector-valued functions.- E. Rothe: Weak topology and calculus of variations.- E.O. Roxin: Problems about the set of attainability.
A. Blaquière: Quelques aspects géométriques des processus optimaux -- C. Castaing: Quelques problèmes de mesurabilité liés à la théorie des commandes -- L. Cesari: Existence theorems for Lagrange and Pontryagin problems of the calculus of variations and optimal control of more-dimensional extensions in Sobolev space -- H. Halkin: Optimal control as programming in infinite dimensional spaces -- C. Olech: The range of integrals of a certain class vector-valued functions -- E. Rothe: Weak topology and calculus of variations -- E.O. Roxin: Problems about the set of attainability.
Electronic reproduction.
Keywords: Calculus of variations